Family Communication In Conflict: Analysis Through Robert Bales' Theory - Nuriyati Nursalam; Swastiningsih; Selamat Ginting; Yuri Alfrin Aladdin; Rara Nareswari Dewanti (Ikatan Sarjana Komunikasi Indonesia, 2025)
This research aims to analyze family communication in conflict. This research uses Robert Bales' Theory, with 6 assumptions that serve as the guide in this study. The paradigm used is Phenomenology, to understand the experiences of each individual. This study analyzes 4 families in conflict, with 6 informants. To maintain family confidentiality, the informants are symbolized as: A, B, C, and D, consisting of a child and one parent. The families analyzed are those who were once married and have since divorced, but must continue to communicate due to the presence of children. The research was conducted through observation, in-depth interviews, and documentation. The research results show that each family has its own way of resolving communication conflicts. Family A is committed to maintaining communication between the child and the separated parents; families B and C experience poor communication situations, which affect the child's adaptation difficulties and various emotional disturbances. The research results show that 2 families experience problems in communication, evaluation, supervision, tension, and cohesion, 1 family experiences problems in communication, evaluation, and supervision, and 1 family can maintain communication, share in evaluation, supervision, and maintain cohesion for the sake of their child even though they have separated as a couple.